2023
DOI: 10.14309/ajg.0000000000002361
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors Suppress Hepatitis C Virus Replication in Infected Patients With Solid Tumors

Abstract: INTRODUCTION: Data are scarce regarding the virologic impact and safety of immune checkpoint inhibitors (ICI) in patients with chronic hepatitis C virus (HCV) infection. We examined the virologic impact of ICI in HCV-infected patients with solid tumors and their safety. METHODS: HCV-infected patients with solid tumor treated with ICI at our institution between April 26, 2016, and January 5, 2022, were enrolled in a prospective observational study. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…[ 31 , 57 ] A prospective study from MD Anderson Cancer Center indicated that ICIs are safe in HCV-infected patients with solid tumors. [ 14 ] In that study, only 2 of 52 patients (4%) treated with ICIs had HCV reactivation, and those patients were also receiving immunosuppressants such as infliximab and high-dose corticosteroids for ICI-related toxic effects, making it difficult to determine if the reactivation was associated with ICI therapy alone. [ 58 ] None of the other studies we found on ICI therapy in HCV-infected patients with cancer showed any cases of HCV reactivation ( Table 4 ).…”
Section: Safety Of Ici S In Patients With Cancer A...mentioning
confidence: 99%
See 3 more Smart Citations
“…[ 31 , 57 ] A prospective study from MD Anderson Cancer Center indicated that ICIs are safe in HCV-infected patients with solid tumors. [ 14 ] In that study, only 2 of 52 patients (4%) treated with ICIs had HCV reactivation, and those patients were also receiving immunosuppressants such as infliximab and high-dose corticosteroids for ICI-related toxic effects, making it difficult to determine if the reactivation was associated with ICI therapy alone. [ 58 ] None of the other studies we found on ICI therapy in HCV-infected patients with cancer showed any cases of HCV reactivation ( Table 4 ).…”
Section: Safety Of Ici S In Patients With Cancer A...mentioning
confidence: 99%
“…Oncologic professional societies recommend universal HCV screening for all patients with cancer. [ 59 , 60 ] Published data [ 6 , 7 , 14 , 23 , 24 , 31 , 32 , 45 , 57 , 61 , 62 ] support that HCV-infected patients with cancer can be safely enrolled in cancer clinical trials of ICIs; however, these patients should be monitored for hepatitis flare and reactivation (or enhanced HCV replication). The management of HCV in patients with cancer receiving ICIs should be individualized on the basis of the patient’s viral hepatitis status, liver function, cancer treatment plan, and cancer status.…”
Section: Recommendations For Managing Hcv Infection In Patients With ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of The American Journal of Gastroenterology , Yibirin et al (5) demonstrate that those with active HCV infection overall have a good prognosis with concomitant ICI therapy and should not only be considered for this type of cancer therapy but also should not be left out from clinical trials using these therapies.…”
mentioning
confidence: 99%